Starlike and Convex Functions Subordinate to Leaf-Like Domain (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of present paper is to find the  Fekete-Szego inequality for the Starlike and Convex functions associated with Leaf-Like domains. Furthermore, similar study has done for convolution of functions.